1989
DOI: 10.1128/mmbr.53.1.68-84.1989
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, biochemistry, and specific inhibitors of CH4, NH4+, and CO oxidation by methanotrophs and nitrifiers.

Abstract: CO +)O + AH. CO. + H,O A (2) NH3 4-OA + AH-NHOH + H.O + A (3) T'he immediate source of reductant (AH.) can be reduced nicotinamide adenine dinucleotide (phosphate) [NAD(P)H] in methanotr-ophs, but in ammonia oxidizeirs it may be a cytochroome c (25. 157). All of the above oxidations are pparently catalyzed by monooxygenase enzymes: methane monooxygenase in methanotrophs and ammonia monooxygenase in ammonia oxidizei-s (25, 61). Only CH4 can support growth in the former organisms. and only NH. can support growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
374
2
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 585 publications
(388 citation statements)
references
References 106 publications
11
374
2
1
Order By: Relevance
“…Michaelis-Menten kinetics of atmospheric CH4 oxidation in upland soil samples were reported in the early 1990s and the observed Km(app) values were in the nanomolar range (Bender and Conrad, 1992;1993;. To that date reported Km(app) values of cultivated methanotrophic species were above 1 mM (Bedard and Knowles, 1989), and comparable values could only be measured in aerated soils when the respective sample was preincubated at concentrations above 50 000 ppmv CH4 (Bender and Conrad, 1992). Furthermore, aqueous extracts containing methanotrophic cells from several acidic forest soils displayed CH4 oxidation optima at pH 5.8 and were not able to oxidize atmospheric CH4 mixing ratios at pH 7.0.…”
Section: The Beginning Of the Questmentioning
confidence: 97%
“…Michaelis-Menten kinetics of atmospheric CH4 oxidation in upland soil samples were reported in the early 1990s and the observed Km(app) values were in the nanomolar range (Bender and Conrad, 1992;1993;. To that date reported Km(app) values of cultivated methanotrophic species were above 1 mM (Bedard and Knowles, 1989), and comparable values could only be measured in aerated soils when the respective sample was preincubated at concentrations above 50 000 ppmv CH4 (Bender and Conrad, 1992). Furthermore, aqueous extracts containing methanotrophic cells from several acidic forest soils displayed CH4 oxidation optima at pH 5.8 and were not able to oxidize atmospheric CH4 mixing ratios at pH 7.0.…”
Section: The Beginning Of the Questmentioning
confidence: 97%
“…The response of methanotrophs to nitrogen has been a major subject of study because of the potential for inhibition of methanotrophs by ammonium and/or nitrite (Hanson and Hanson, 1996). Numerous studies have shown, using pure cultures, microcosms and field trials, that nitrogen additions decrease methane oxidation (Bedard and Knowles, 1989;Conrad and Rothfuss, 1991). On the other hand, recent rice microcosm studies (Bodelier and Frenzel, 1999;Bodelier et al, 2000) have clearly shown that N fertilization increases methane oxidation in densely rooted rice soil.…”
Section: Effect Of Rice Plants On Methanotroph Populationsmentioning
confidence: 99%
“…However, AMO is much less efficient than MMO in CH 4 oxidation, so about a thousand AOB cells are needed to achieve the same rate of CH 4 oxidation as a single MB cell (Jiang and Bakken, 1999). Thus, AOB apparently do not play an important role in CH 4 uptake by soils (Bedard and Knowles, 1989;Bender and Conrad, 1994;Bodelier and Frenzel, 1999). Bender and Conrad (1992) first suggested that the MB active in upland soils were not known species.…”
Section: Introductionmentioning
confidence: 99%